Arthroscopic Remplissage Using a Double-Pulley System for Hill-Sachs Lesions for Recurrent Shoulder Instability - Woodall, Brittany M. (Arthrosc Tech, 2018)
Hills-Sachs lesions are bony lesions in the humeral head that occur as a result of an anterior shoulder dislocation. These lesions often happen in conjunction with tears of the labrum, and large, engaging lesions must be addressed in order to avoid recurrent instability. Moderate to large (≥3 mm deep) Hill-Sachs defects can be treated using arthroscopic remplissage to reduce the rotator cuff down into the lesion. We describe in this Technical Note and accompanying video an adaptation of the classic arthroscopic remplissage that uses a knotless double-pulley technique with 2 suture anchors, which increases the footprint of fixation, reduces the technical difficulty of the procedure, and minimizes the number of portals that need to be made.